Law's dominion: Jewish community, religion, and family in early modern Metz - Berkovitz, Jay R. (Studies in Jewish history and culture, 2020)
Jewish History through a Legal Lens -- The Foundations of the Metz Kehillah -- Communal Autonomy and Governance -- Lay and Rabbinic Judicial Authority -- Navigating the Challenges of Multiple Jurisdictions -- Guardianship and Inheritance -- Women, Marriage, and Property.